Problems and solutions for the management of production processes in a digitalised economy - A. V. Nikonorova (Вестник университета)
The article reveals and characterises contemporary problems arising in the organisation of production process management, and most forward-looking solutions in conditions of economy’s digitalisation. The article describes the main difficulties that arise when introducing information systems into activities of domestic industrial enterprises. For the first time, an author’s model for the development of a production process management system is presented, considering the plans and current capabilities of the enterprise. Expansion the possibilities of using production process management systems is based on integration of information systems and software used to realise a company’s current objectives, its strategic plans and a contemporary concept ESG. The issues of ensuring safety in production process’ control systems are considered. The development of methods for expanding the possibilities of using information systems increases the manageability of the enterprise, aides in decision making.